A transient increase in MHC-IIlow monocytes after experimental infection with Avibacterium paragallinarum (serovar B-1) in SPF chickens - Alvarez, Karla Lucía F. (2020)
Infectious coryza (IC), an upper respiratory tract disease affecting chickens, is caused by Avibacterium paragallinarum. The clinical manifestations of IC include nasal discharge, facial swelling, and lacrimation. This acute disease results in high morbidity and low mortality, while the course of the disease is prolonged and mortality rates are increased in cases with secondary infections. Studies regarding the immune response in infected chickens are scarce, and the local immune response is the focal point of investigation. However, a large body of work has demonstrated that severe infections can impact the systemic immune response. The objective of this study was to evaluate the systemic effects of Avibacterium paragallinarum (serovar B-1) infection on immune cells in specific pathogen-free (SPF) chickens. The current study revealed the presence of a transient circulating monocyte population endowed with high phagocytic ability and clear downregulation of major histocompatibility complex class II (MHC-II) surface expression. In human and mouse studies, this monocyte population (identified as tolerant monocytes) has been correlated with a dysfunctional immune response, increasing the risk of secondary infections and mortality. Consistent with this dysfunctional immune response, we demonstrate that B cells from infected chickens produced fewer antibodies than those from control chickens. Moreover, T cells isolated from the peripheral blood of infected chickens had a lower ability to proliferate in response to concanavalin A than those isolated from control chickens. These findings could be related to the severe clinical signs observed in complicated IC caused by the presence of secondary infections.